2004
DOI: 10.1242/jcs.00898
|View full text |Cite
|
Sign up to set email alerts
|

The Q267E mutation in the sodium/iodide symporter (NIS) causes congenital iodide transport defect (ITD) by decreasing the NIS turnover number

Abstract: The Na+/I- symporter (NIS) is a key plasma membrane glycoprotein that mediates active iodide (I-) transport in the thyroid and other tissues. Since isolation of the cDNA encoding NIS (G. Dai, O. Levy, and N. Carrasco (1996) Nature 379, 458-460), ten mutations in NIS have been identified as causes of congenital iodide transport defect (ITD). Two of these mutations (T354P and G395R) have been thoroughly characterized at the molecular level. Both mutant NIS proteins are inactive but normally expressed and correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 35 publications
2
37
2
1
Order By: Relevance
“…1 A, D, and G and 4A). In contrast to the many NIS mutants we have studied previously (13)(14)(15)(16)(17)19), substitutions at position 93 show a significant change in the K m for I − . This is true for not only the neutral residues Thr, Asn, and Gln (Fig.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…1 A, D, and G and 4A). In contrast to the many NIS mutants we have studied previously (13)(14)(15)(16)(17)19), substitutions at position 93 show a significant change in the K m for I − . This is true for not only the neutral residues Thr, Asn, and Gln (Fig.…”
Section: Discussioncontrasting
confidence: 81%
“…S1). The mutants that have been studied in detail have provided key mechanistic information on NIS (13)(14)(15)(16)(17). For example, substitutions at T354 have revealed that this position requires an -OH group at the β-carbon, which we showed is involved in Na þ binding/translocation, and proposed a structural homology between the Aquifex aeolicus Na þ ∕leucine transporter (LeuT) (18) and NIS, despite a lack of sequence homology (19).…”
mentioning
confidence: 87%
“…Biotinylation of cell surface proteins was performed as previously described (24). Briefly, transfected cells were incubated with 1 mg/mL of the membrane-impermeable biotin reagent sulfo-NHS-SS-biotin (Pierce Chemical), which covalently interacts with extracellular primary amines.…”
Section: Methodsmentioning
confidence: 99%
“…autosomal recessive condition that results from NIS being either inactive (22)(23)(24) or not targeted to the plasma membrane (16,17,25,26). The resulting impairment in I − uptake in the thyroid leads to congenital hypothyroidism, which, unless treated early in life by TH administration, causes goiter and even mental retardation.…”
Section: Significancementioning
confidence: 99%
“…Congenital hypothyroidism due to impaired iodide uptake has long been described in the literature; however, NIS mutations were recognized only after the cloning of NIS cDNA, and correspond to point mutations [G93R, Q267E, C272X, T354P, Y531X, G543E, G395R, V59E or frameshift (515X)]. Functional studies have already been done for some mutated NIS and have confirmed the following changes in NIS molecular characteristics: loss of function of the protein (T354P, G395R), partial activity (Q267E) or impaired targeting of the protein to the plasma membrane (G543E) (81,82).…”
Section: Congenital Hypothyroidismmentioning
confidence: 99%